2014
DOI: 10.1177/0284185113508114
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of myxoid liposarcoma by magnetic resonance imaging: a histopathologic correlation

Abstract: Tumor components with contrast-enhancing non-fatty, non-myxoid imaging features were predominantly found in high-grade myxoid liposarcomas, which may histologically resemble round cell clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…It has been reported that both benign and malignant STTs may have a myxoid tumor matrix, which is characterized by abundant free water in the extracellular spaces, significantly increasing the ADC values (5,(26)(27)(28)(29). For these reasons, we decided to compare IVIM DWI and DCE MRI parameters among patients with and without myxoid tumors; consistent with previous studies (27,35), the differences in ADC values were strongly significant, as were the differences in D values.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…It has been reported that both benign and malignant STTs may have a myxoid tumor matrix, which is characterized by abundant free water in the extracellular spaces, significantly increasing the ADC values (5,(26)(27)(28)(29). For these reasons, we decided to compare IVIM DWI and DCE MRI parameters among patients with and without myxoid tumors; consistent with previous studies (27,35), the differences in ADC values were strongly significant, as were the differences in D values.…”
Section: Discussionsupporting
confidence: 65%
“…Our IVIM DWI and DCE MRI results confirmed the wide heterogeneity in both diffusion and perfusion parameters of STTs. According to previous studies , very high ADC and D values were found for myxoid lesions as a result of the presence of abundant free water in the extracellular spaces of the tumor matrix. The lowest ADC and D values were found primarily for malignant tumors, such as undifferentiated pleomorphic sarcomas and malignant schwannomas, which are characterized by increased nIAUGC and MSI.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The 2013 WHO classification accordingly discarded the term ‘round cell liposarcoma’ from the classification. These tumors are now considered to represent high-grade myxoid liposarcoma, with the prognosis worsening with increasing round cell component (> 5%) (192526). …”
Section: Liposarcomamentioning
confidence: 99%
“…Macroscopic fat is the clincher if observed on imaging, but may constitute < 10% of tumor volume and may be difficult to visualize on imaging (192527). Visualization of a non-fatty non-myxoid enhancing component may correspond to the round cell component, if present, and should be targeted for biopsy (2526). Given the presence of these various components, visualization of a true ‘cyst mimic’ (a tumor which could be misdiagnosed as a cyst without administering intravenous contrast) is uncommon (20).…”
Section: Liposarcomamentioning
confidence: 99%